DAILY CHANGES OF CENTRAL HEMODYNAMICS IN PATIENTS WITH CHRONIC HEART FAILURE WITH NIGHT-TIME DYSPNOEA ATTACK - S. A. Dovgolis; I. G. Fomina (Столичная издательская компания, 2016)
Aim. To study daily changes of central hemodynamics (CHD) in patients with chronic heart failure (CHF) and the effects of therapy. Materials and methods. 22 patients with ischemic heart disease and CHF of III-IV functional class (FC) by NYHA, age 60,5±10,5 were observed. Patients were suffering from night-time dyspnoea attacks and had pulmonary artery occlusion pressure (PAOP) 15-20 mm Hg. CHD was monitored invasively before the treatment and after 4 weeks of CHF treatment. Results. According to the cardiac index (CI) at admission patients were split into two groups. 9 patients of group-I had CI ≤2,15 l\min\m2, and 13 patients of group-II had CI >2,15 l\min\m2. In patients of group-I CI increased in 4 weeks of treatment. The treatment caused considerable clinical improvement in all patients. The CHD indexes also improved. Initially evening-night-time peaks of PAOP (р≤0,002), systolic (SBP) (р≤0,003), diastolic (DBP) (р=0,002) and average (BPa) (р=0,0007) blood pressure (BP) as well as double multiplication (DM) (р≤0,008) were registered in patients of group-I. At the end of treatment only evening-night increase in DBP (р=0,002) and BPa (р≤0,006) were noted. In patients of group-II after 4 weeks of treatment CI decreased or didn't change. Towards 28-th day of treatment 10 patients had clinical improvements. Only one patient's FC NYHA increased. At the end of treatment the normalization of CHD was registered totally in group. Initially evening-night-time peaks of PAOP (р≤0,002), SBP (р≤0, 0001), CI (р=0,057) and DM (р=0,084) were registered in patients of group-II. At the end of treatment evening-night-time peaks of PAOP (р≤0,015), SBP (р≤0,044), CI (р≤0,005) and DM (р≤0,044) still remained. Besides, evening-night-time peaks of cardiac output (р≤0,01) and systolic index (р≤0, 06) have added. Conclusion. In patients with CHF with initial CI ≤2,15 l\min\m2 treatment results in the normalization of CHD and its daily rhythm. In patients with CHF with initial CI >2,15 l\min\m2 the treatment leads to the normalization of CHD, though it doesn't correct daily rhythm disturbances of circulation.